Sosialisasi Dampak Kegiatan Kuliah Kerja Nyata Di Desa Sungai Bulian - Rahmi Safitri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Community Service Program (KKN) is a form of learning in the form of community service carried out by a group of students with the aim of advancing community welfare and educating the nation's life. The purpose of implementing KKN is to apply, practice, and cultivate knowledge and technology to promote public welfare and educate the nation's life, as well as to provide practical experience for participants in applying theory and practice. The method used for implementation is the socialization method. Based on the results and conclusions of the KKN activities carried out in Sungai Bulian Village, Tabir Timur District, Merangin Regency, the community service program has been running well according to the expected procedures. This activity is very important for students and the environment they are in because they are required to adapt to the environment, atmosphere, place of residence, and the language used daily.